Assessment of the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire for use in patients after neck dissection for head and neck cancer. Issue 2 (26th September 2014) - Goldstein, David P.; Ringash, Jolie; Irish, Jonathan C.; Gilbert, Ralph; Gullane, Patrick; Brown, Dale; Xu, Wei; Del Bel, Ryan; Chepeha, Douglas; Davis, Aileen M.
Abstract Background In this cross‐sectional study, the sensibility, test‐retest reliability, and validity of the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire were assessed in patients who underwent neck dissection. Methods Sensibility was assessed with a questionnaire. Test‐retest reliability was performed with completion of the DASH questionnaire 2 weeks after initial completion; validity, by evaluating differences in scores between patients undergoing different types of neck dissections and correlating DASH scores with Neck Dissection Impairment Index (NDII) scores. Results The DASH questionnaire met sensibility criteria. For test‐retest reliability analysis, the intraclass coefficient was 0.91. The DASH questionnaire showed differences between patients who underwent accessory nerve‐sacrifice and nerve‐sparing neck dissection. DASH questionnaire scores strongly correlated with NDII scores (r = ‐0.86). Conclusion Although this study provides preliminary data on some psychometric properties of the DASH questionnaire in patients who have undergone a neck dissection, further assessment of responsiveness and other properties are required. © 2014 Wiley Periodicals, Inc. Head Neck37: 234‐242, 2015